Total fats and fatty acids consumption by sportsmen practicing slalom canoe and sport-shooting - Nowacka, E.; Kopec, A.; Leszczynska, T.; Polaszczyk, S.; Pysz, K. (Science & Sports, 2013)
Objective: The objective of this study was to estimate the total fat, saturated, monounsaturated, polyunsaturated fatty acids and cholesterol intake by sportsmen practicing slalom canoe racing and sport-shooting. Material and methods: The studies were performed at 29 slalom canoe's racing and at 23 sport's shooting sportsmen. Twenty-four-hour dietary recalls were collected in training and start period of 2009, for three selected days per week (including Friday and Sunday, due to the different, eating habits in Poland). Results: The obtained amount of total fats intake in average daily diet of canoeist and shooters were 29% and 34% of total energy, respectively. The saturated fatty acids delivered -16% and 17% of total energy, respectively. The percentage of monounsaturated fatty acids was in accordance with recommendations (above 10% of total energy of daily diets), whereas for n-3 family polyunsaturated fatty acids, especially the docosahexaenoic acid and eicosapentaenoic acid, were too low (below 1% of energy of daily diets). However the proper ratio of n-6 to n-3 (5-6:1) were found. Conclusions: It is therefore reasonable to increase consumption of fatty sea fish, canola and flax seeds oil rich in n-3 family fatty acids by sportsmen.